2010
DOI: 10.1002/nag.870
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic yielding and cyclic behavior of geomaterials

Abstract: SUMMARYIn this paper, the novel concept of probabilistic yielding is used for 1-D cyclic simulation of the constitutive behavior of geomaterials. Fokker-Planck-Kolmogorov equation-based probabilistic elastic-plastic constitutive framework is applied for obtaining the complete probabilistic (probability density function) material response. Both perfectly plastic and hardening-type material models are considered. It is shown that when uncertainties in material parameters are taken into consideration, even the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The most general, rate form of the constitutive equation for an uncertain, elastic‐plastic material, when written in the probability density space, becomes 2 coupled FPK PDEs of the following forms: rightP(σ,t)tleft=σmnN(1)mnσeq(σ,q;t)P(σ,t)rightrightleft+2σmnσabN(2)mnabσeq(σ,q;t)P(σ,t), rightP˜(q,t)tleft=qiN(1)iIVeq(σ,q;t)P˜(q,t)rightrightleft+2qiqjN(2)ijIV…”
Section: The Fpk Equations In Probabilistic Elasto‐plasticitymentioning
confidence: 99%
See 3 more Smart Citations
“…The most general, rate form of the constitutive equation for an uncertain, elastic‐plastic material, when written in the probability density space, becomes 2 coupled FPK PDEs of the following forms: rightP(σ,t)tleft=σmnN(1)mnσeq(σ,q;t)P(σ,t)rightrightleft+2σmnσabN(2)mnabσeq(σ,q;t)P(σ,t), rightP˜(q,t)tleft=qiN(1)iIVeq(σ,q;t)P˜(q,t)rightrightleft+2qiqjN(2)ijIV…”
Section: The Fpk Equations In Probabilistic Elasto‐plasticitymentioning
confidence: 99%
“…The most general, rate form of the constitutive equation for an uncertain, elastic-plastic material, when written in the probability density space, becomes 2 coupled FPK PDEs of the following forms 3,4,8,9,16 :…”
Section: The Fpk Equations In Probabilistic Elasto-plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that by considering the uncertainty in yield stress, the average (mean) constitutive response and the most probable (mode) constitutive response show nonlinear behavior from the very beginning, even for the simplest elastic-perfectly plastic material model [18]. To make this method more general, Sett and Jeremi´c also discussed the effect of probabilistic yielding on constitutive simulation under cyclic loading [19] . In 2014, Sadrinezhad and Sett extended the one-dimensional framework to a multi-dimensional framework to simulate the probabilistic elastic plastic constitutive behaviour of soils [20,21].…”
Section: Introductionmentioning
confidence: 99%